PEMEKARAN DAERAH DAN PERSOALAN GOVERNABILITY LOKAL DI INDONESIA - Tryatmoko, Mardyanto Wahyu (Jurnal Penelitian Politik, 2010)
The implementation of regional government splitting or proliferation in Indonesia has created many acuteproblems in the local level These problems refer to local ungovernability problem ofgovernability This paperargues that the problem oflocal governability caused by proliferation policy occurs in both governing and governed The weakness ofcivil society marked by lessening of its participation is an indicator of diminishing consentof society Meanwhile corruption bureaucratic and political rent seeking are indicators of the weaknesses ofgoverning capacity